TINDAK PIDANA NARKOTIKA SEBAGAI TINDAK PIDANA KHUS: ANALISIS YURIDIS TERHADAP URGENSI PENEGAKAN HUKUM DAN OPTIMALISASI KEBIJAKAN REHABILITASI DI INDONESIA - Kadek Jodi Krisnantara; Made Sugi Hartono; Ni Putu Ega Parwati (Universitas Pendidikan Ganesha, 2026)
Narcotics as a special criminal offense under Law No. 35 of 2009 has distinct characteristics compared to general crimes in the Indonesian Penal Code, such as minimum sentencing, reversed burden of proof, and the principle of ultimum remedium. However, law enforcement practice in Indonesia still shows imbalance between repressive approaches through imprisonment and restorative approaches through rehabilitation for users and addicts. This study aims to analyze the urgency of law enforcement and the optimization of rehabilitation policies for narcotics crimes as special criminal offenses. The research method used is normative juridical with statutory, conceptual, and court decision analysis approaches. The findings indicate that the urgency of law enforcement remains necessary to create a deterrent effect on traffickers and dealers, while rehabilitation should be prioritized for users and addicts in accordance with the objectives of the Narcotics Law and Supreme Court Circular Letter No. 4 of 2010. The lack of consistency in judicial decisions, limited rehabilitation facilities, and social stigma are the main obstacles to optimizing rehabilitation policies. It is concluded that narcotics law enforcement in Indonesia needs to integrate a dual paradigm: repressive toward perpetrators of illicit trafficking and rehabilitative toward victims of abuse, so that the objectives of punishment and recovery can be achieved proportionally.